Hippocampal structural plasticity accompanies the resulting contextual fear memory following stress and fear conditioning - Giachero, Marcelo (2013)
The present research investigated the resulting contextual fear memory and structural plasticity changes in the dorsal hippocampus (DH) following stress and fear conditioning. This combination enhanced fear retention and increased the number of total and mature dendritic spines in DH. Intra-basolateral amygdala (BLA) infusion of midazolam prior to stress prevented both the enhancement of fear retention and an increase in the density of total and mature dendritic spines in DH. These findings emphasize the role of the stress-induced attenuation of GABAergic neurotransmission in BLA in the promoting influence of stress on fear memory and on synaptic remodeling in DH. In conclusion, the structural remodeling in DH accompanied the facilitated fear memory following a combination of fear conditioning and stressful stimulation.